ANALISIS PERANAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN MIMIKA - Sisca .; Habel Taime (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2019)
This study aims to determine the development of the Mimika Regency retribution in 2007-2015, and the role of regional retribution on Mimika Regency original income in 2007-2015. In processing the data obtained in this study, the instruments of data analysis tools used were the analysis of the effectiveness of retribution receipts, the rate of growth in retribution receipts, and the contribution of retribution receipts to PAD. The results of this study indicate that: (1) The average effectiveness of receipts for the Mimika Regency retribution for 2007 - 2015 analyzed according to its group is 120.42% (very effective) for public service levies 91.02% (effective) for the class of retribution business services, and 119.57% (very effective) for certain categories of licensing fees. Overall, the average effectiveness of receipts for the Mimika Regency retribution for 2007 - 2015 was 113.88% with a very effective category; (2) The growth rate of receipt of Mimika Regency retribution during 2007-2015 which was analyzed according to its class was very fluctuating, even reaching a negative growth rate; (3) The average contribution of regional levies to the Mimika Regency PAD during 2017-2015 which was analyzed according to its group was 3.53% (very low) for the general service charge group, 0.96% (very low) for the retribution group. business services, and 4.24% (very low) for certain licensing fees. Overall, the average contribution of regional retribution to Mimika Regency's regional income during 2007 - 2015 was 8.73% with very low criteria.